Ecosystem services provided by hay meadows in Iberian mountain areas: evolution and perspectives - García-de-la-Fuente, Laura (2019)
Hay meadows represents agro-ecosystems maintained by secular extensive management of rural communities throughout Europe. Their progressive disappearance (especially in mountain areas) represents a significant loss of biodiversity and ecosystem services. This study aimed at carrying out a general diagnosis of ecosystem services (ES) provided by hay meadows in the Iberian Peninsula, focusing on mountain areas located in the North of Spain and Portugal, most of which are currently protected areas or/and Natura 2000 sites. The conceptual framework developed in the Millenium Ecosystem Assessment has been applied to characterise and assess the most relevant ES, as well as to analyse their evolution and driving forces in the last decades, based on published data and expert opinion. As the area of hay meadows has been decreasing notably over the last 60 years in this area, a general loss in the supply of fundamental ES for the well-being of our society is taking place. The study also briefly discusses possible responses to tackle this decline.